2019
DOI: 10.1038/s41467-019-08637-9
|View full text |Cite
|
Sign up to set email alerts
|

A functional subset of CD8+ T cells during chronic exhaustion is defined by SIRPα expression

Abstract: Prolonged exposure of CD8+ T cells to antigenic stimulation, as in chronic viral infections, leads to a state of diminished function termed exhaustion. We now demonstrate that even during exhaustion there is a subset of functional CD8+ T cells defined by surface expression of SIRPα, a protein not previously reported on lymphocytes. On SIRPα+ CD8+ T cells, expression of co-inhibitory receptors is counterbalanced by expression of co-stimulatory receptors and it is only SIRPα+ cells that actively proliferate, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 81 publications
(92 reference statements)
0
50
1
Order By: Relevance
“…Our findings show that low DCLK1 expression correlated with high or low CD8 + T cells predicts better survival in colon and stomach cancer patients, suggesting DCLK1 has the potential to be an adjuvant target to promote sensitivity in immunotherapy-resistant patients. Additionally, it is widely reported that exhausted CD8+ T cells also express CD8A but lose the ability to eradicate the tumor cell [86,87]. This is hypothesized to be one significant reason why immune blockade increases the function of exhausted CD8+ T cells [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that low DCLK1 expression correlated with high or low CD8 + T cells predicts better survival in colon and stomach cancer patients, suggesting DCLK1 has the potential to be an adjuvant target to promote sensitivity in immunotherapy-resistant patients. Additionally, it is widely reported that exhausted CD8+ T cells also express CD8A but lose the ability to eradicate the tumor cell [86,87]. This is hypothesized to be one significant reason why immune blockade increases the function of exhausted CD8+ T cells [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SIRP was also reported to be selectively expressed on a small subset of T lymphocytes, i.e. exhausted CD8+ memory T cells emerging after chronic viral infection (Myers et al, 2019). For a long time the general assumption has been that SIRP is, at least among hematopoietic cells, restricted to the myeloid lineage (Adams et al, 1998;Brooke et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence most FVspecific CD8+ T cells appear functionally exhausted and are very inefficient in killing peptide-labeled targets in vivo (Zelinskyy et al 2009a). However, a small subset of functional CD8+ T cells are preserved even in chronic infection and uniquely express the cell surface protein SIRPα (Myers et al 2019). CD8+ T cell exhaustion contributes to the subsequent development of FV chronicity , similar to what has been described for chronic LCMV infection (Barber et al 2006).…”
Section: Cd8+ T Cell Responsesmentioning
confidence: 99%
“…During chronic infection PD-1 expression can be used as a surrogate marker for exhausted CD8+ T cells and blocking the signaling of this receptor with antibodies can reactivate exhausted T cells (Barber et al 2006;Dietze et al 2013). Blocking the PD-1/PDL-1 axis results in the expansion of functional CD8+ T cells that express SIRPα (Myers et al 2019). Increased expression of co-inhibitory molecules such as PD-1 is likely to prevent immunopathogenic effects from overstimulated CD8+ T cells responses.…”
Section: Cd8+ T Cell Responsesmentioning
confidence: 99%
See 1 more Smart Citation